PELATIHAN GURU MENGENAI LITERASI DAN ASESMEN KEMAMPUAN LITERASI - Meicky Shoreamanis Panggabean; Atalya Agustin (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Abstract The world of education changes as the impact of Industrial Revolution 4.0. All parties experience rapid changes and transformations in the fields of information, technology, and communication. After learning is carried out remotely due to the pandemic, teachers have different needs that should be accommodated. This decision to meet their needs have to be made because blended learning will take place due to the increasingly developing technology and the new normal faced by the world of education. Professional Development Program is a great way to help teachers improve these skills on an ongoing basis which has an impact on teachers and education in general. The proposed program aims to provide training to teachers in literacy and assessment according to the current educational context. Keywords: industrial revolution; teacher skills; literacy; assessment